Online Teaching using Video-Based Technology in Teaching Health Education due to Malaysian Movement Control Order - Gengatharan, Kumaran; Rahmat, Azali Bin; Krishnan, Szarmilaa Dewie (International Journal of Psychosocial Rehabilitation, 2020)
Video-based teaching is one of the teaching methods or technology widely used in different fields. This method helped effectively in the process of teaching and learning (Simin Ghavifekr & Wan Athirah Wan Rosdy, 2015[1]. The aim of the article mainly focused on the importance of video-based technology in teaching Health Education due to the Malaysian movement control order for year five students. A self- made video about the topics in Health Education was constructed, and it was uploaded in Google drive. The link of the video was shared with year five students via google mail. The videos were made in Windows Live Movie Maker, which allows frame-by-frame playback of the video. The materials used in this research are the laptop and the video making software. The instrument used is a questionnaire to identify the importance of video-based technology in teaching Health Education. Analysis towards the data of this study was done using ‘SPSS’ version 22. Research findings show that the students are more interested in video-based teaching, and the students felt video-based teaching is more effective than face- to-face teaching. In conclusion, results proved that video-based teaching is very imperative and essential for year five students in learning Health Education subject. Not that only, data obtained from the questionnaire show that 95.5 percent of students felt learning Health Education using video-based technology is more effective.